(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Changes in our society have created necessary conditions for updating the entire educational system, which is reflected in the development and introduction of new content elements, new educational technologies, and reference to world pedagogical experience. As the Republic of Uzbekistan is on the way to building a legal democratic society, it pays special attention to the development of its citizens, especially the young generation who are determined to build a new society. Development of a child’s creative abilities with the help of visual arts is a process that combines various spheres of activity and is manifested in interrelated elements. The systematic use of interactive technologies in visual art classes develops the following personal qualities: spatial thinking, a sharp sense of color, eye vigilance, forms the qualities of human intelligence, ultimately, they are important not only in creativity. is a drawing, sketch, or model of an object. These qualities include, first of all, figurative imagery and logical thinking, which are a prerequisite for creativity in any human activity.